Underground water resources: analysis of wells from rodeio (SC) (Revista Brasileira de Contabilidade e Gestão, 2014)
To identify the quality of the groundwater of the municipality of Rodeio – Santa Catarina and its potability for human consumption, water samples were collected in the second half of 2014 from ten common and semi-artesian wells distributed in the municipality and analyzed with experimental research regarding physical-chemical and microbiological parameters. To translate the quantitative data studied into qualitative and thus determine the potability of the liquid, documentary analysis was carried out comparing the results obtained with CONAMA Resolution 396/2008 and with Ordinance MS 2914/2011. Among the wells analyzed, seven presented thermotolerant coliforms and five had low pH. With 95% confidence, the pH of groundwater from Rodeio (SC) is in the range of 5.56 to 6.41. Thus, 80% of the wells analyzed presented inadequate and harmful characteristics to human health.
Keywords: wells; water analysis; underground water resource; water resources